Prognostic value of left atrial strain in acute and chronic heart failure: A meta‐analysis - Maria Concetta Pastore; Mariangela Vigna; Andrea Saglietto; Maria Alma Iuliano; Giulia Elena Mandoli; Andrea Stefanini; Chiara Carrucola; Laura Fusini; Luna Cavigli; Flavio D'ascenzi; Marta Focardi; Serafina Valente; et al. (ESC Heart Failure, 2025)
Abstract Aims Heart failure (HF) is a global health burden which prognostic assessment is currently challenging. Speckle tracking left atrial strain is widely recognized as a predictor of HF outcome. Our aim was to systematically investigate the prognostic value of peak atrial longitudinal strain (PALS) in acute and chronic HF and according to left ventricular (LV) function, age and gender. Methods and results A systematic literature search of medical databases was performed using PRISMA principles. All relevant studies reporting the prognostic value of LA strain in HF with reduced, mildly reduced and preserved ejection fraction (EF) with ≥6 months follow‐up were included. All‐cause mortality and HF hospitalization were considered as primary endpoint. Random‐effect meta‐analysis was performed to evaluate the pooled hazard ratios (HR) of the primary outcome. Eight studies (n = 5767 patients, median [interquartile range] age = 66.3 [65; 68.6]) satisfied the inclusion criteria (five chronic HF, two acute HF and one both). Median global PALS was 17.6 [14.9; 26.8]%, median LVEF was 36 [30; 56]%, median left ventricular global longitudinal strain (GLS) was −9% [−7; −16.9]. Over a median follow‐up of 903 [321; 1062] days, 2688 patients reached the primary endpoint (944 all‐cause mortality and 1963 hospitalizations). Each unit decrease in global PALS was independently associated with 5% increase for the primary endpoint (meta‐analytic HR = 1.05; 95% CI [1.02–1.07]; P < 0.01). Subgroup analysis showed no differences in acute and chronic HF (P = 0.18). Meta‐regression analysis showed a higher prognostic value of global PALS for lower values of LVEF (beta = −0.0023). Conclusions Global PALS may be used as prognostic tool in acute and chronic HF and especially in patients with reduced EF, providing an additional independent value for risk stratification in clinical practice.